A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae) - Britz, Ralf; Ferraris, Jr., Carl J. (Zootaxa, 2003)
A new species of the erethistid catfish genus Pseudolaguvia from Myanmar is described. Pseudolaguvia tenebricosa, new species, from Pathe Chaung, Lower Myanmar, differs from the only congener P. tuberculata (Prashad & Mukerji, 1929) in having an adipose fin not reaching dorsal fin, and a narrower head with a shorter snout.